Comparing muscle Vo2 from near-infrared spectroscopy desaturation rate to pulmonary Vo2 during cycling below, at, and above the maximal lactate steady state - de Almeida Azevedo, R.; Forot, J.; Millet, G. Y.; Murias, J. M. (Journal of Applied Physiology, 2022)
Muscle oxygen uptake (Vo2m) evaluated from changes in the near-infrared spectroscopy oxygen desaturation slope during a 5-s arterial blood flow occlusion has been proposed as an estimation of the actual Vo2m. However, its correspondence with pulmonary oxygen uptake (Vo2p) during exercise remains unknown. This study investigated the Vo2m and Vo2p relationship in females and males in response to prolonged constant-load cycling exercise at different intensities. Eighteen participants (8 females) visited the laboratory on six occasions: 1) ramp incremental test; 2 and 3) 30-min constant power output (constant-PO) exercise bout to determine the maximal lactate steady state (MLSS); 4-6) constant-PO exercise bouts to task failure at i) 15% below MLSS (MLSS-15%); ii) MLSS; and iii) 15% above MLSS (MLSS+15%). Vo2m was estimated at baseline, at min 5, min 10, min 20, min 30, and at task failure. Vo2p was continuously recorded during the constant-PO bouts. Vo2p and Vo2m significantly increased from min 5 to min 30 in MLSS condition (all P values <0.05) and from min 5 to min 10 in MLSS+15% condition (all P < 0.05). Vo2p and Vo2m were correlated (r2adj range of 0.70-0.98, all P < 0.001) among exercise intensities in both females and males. In addition, both variables were also correlated when expressed as percent (r2adj range of 0.52-0.77, all P < 0.001). Vo2p and Vo2m responses were similar when exercising below, at, and above the MLSS independently of sex. Most importantly, Vo2p and Vo2m were correlated regardless the exercise intensity and sex of the participants.